Adopt E-Mental Health Services: Factors Shaping Intention to Engage - Samsudin, Rahimah; Khan, Nasreen; Subbarao, Anusuyah; Chen, Tan Booi Chen Booi; Obreja, Serban Georgică (JOIV : International Journal on Informatics Visualization, 2025)
E-Mental Health (eMH) tools are increasingly vital in providing scalable mental health support. This study aims to examine the factors influencing users’ intention to engage with eMH services. Specifically, it investigates the effects of six reflective first-order dimensions: Accessibility, Communication, Affordability, Flexibility, Custom Belief, and Government Support on the reflective second-order construct: Intention to Engage in E-Mental Health. Using data from 100 respondents, Partial Least Squares Structural Equation Modelling (PLS-SEM) was employed to test the hypothesized relationships and assess the strength of each contributing factor. The results show that Accessibility, Communication, and Flexibility are the most influential predictors of engagement. Affordability and Custom Belief demonstrate moderate but positive impacts, while Government Support plays a complementary role. These findings provide critical insight into user-centered design priorities for eMH platforms, particularly in enhancing user retention and accessibility. Practical applications include the development of multilingual mobile applications, culturally adaptive cognitive-behavioral therapy tools, and enhanced digital communication pathways. This study contributes to the understanding of how both infrastructural and personal belief factors can drive engagement. It also highlights the importance of holistic system support in digital mental health ecosystems. For future research, it is recommended to explore user engagement across diverse demographic and cultural settings and to examine the effectiveness of emerging technologies such as AI-driven chatbots and virtual reality therapies. Additionally, policy-level interventions should be further evaluated to strengthen the implementation and sustainability of digital mental health services.